2012
DOI: 10.1530/erc-12-0142
|View full text |Cite
|
Sign up to set email alerts
|

Insulin resistance and cancer: epidemiological evidence

Abstract: Epidemiological research into insulin resistance has focused on excess body weight, type 2 diabetes mellitus (DM), physical activity, and coffee consumption. These common modifiable factors have also been suggested to play a role in the process of carcinogenesis via associations with insulin resistance. Findings of systematic literature reviews and meta-analyses have generally supported an association between excess body weight and DM with an increased risk of colon cancer in males, and of liver, pancreatic, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
53
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 87 publications
(55 citation statements)
references
References 60 publications
0
53
0
2
Order By: Relevance
“…After reviewing several studies, Crimmins et al (Crimmins and Martin, 2007) reported that rs1342387 was the only single nucleotide polymorphism (SNP) of adiponectin receptor 1 which was significantly associated with HOMA-IR as a measure of insulin resistance. Present studies had shown that obesity and insulin resistance were risk factors of kinds of cancers (Inoue and Tsugane, 2012;Vucenik and Stains, 2012). And Insulin levels were shown to be correlated with the expression of adiponectin receptors (Tsuchida et al, 2004), which could be downregulated by obesity and in turn lead to insulin resistance (Ouchi et al, 2000).…”
Section: Discussionmentioning
confidence: 97%
“…After reviewing several studies, Crimmins et al (Crimmins and Martin, 2007) reported that rs1342387 was the only single nucleotide polymorphism (SNP) of adiponectin receptor 1 which was significantly associated with HOMA-IR as a measure of insulin resistance. Present studies had shown that obesity and insulin resistance were risk factors of kinds of cancers (Inoue and Tsugane, 2012;Vucenik and Stains, 2012). And Insulin levels were shown to be correlated with the expression of adiponectin receptors (Tsuchida et al, 2004), which could be downregulated by obesity and in turn lead to insulin resistance (Ouchi et al, 2000).…”
Section: Discussionmentioning
confidence: 97%
“…IR is a condition in which the body produces sufficient insulin to take up and use glucose, but the sensitivity to this insulin is impaired or selective, thus causing pancreatic b-cells to upregulate insulin production as a compensatory mechanism, which results in hyperinsulinemia. There are several studies linking hyperinsulinemia and the risk and/or aggressiveness of colorectal, pancreatic, liver, esophageal, breast, and endometrial cancers (Gunter et al 2008, Arcidiacono et al 2012, Inoue & Tsugane 2012, Qiu et al 2012, Zhan et al 2013. Thyroid nodules follow the same trend (Rezzonico et al 2008).…”
Section: Ir and The Role Of Igf1mentioning
confidence: 99%
“…Metabolic syndrome and insulin resistance have been associated with increased risk of cancer, including cardia gastric cancers (42,43). This is mediated by adipokines and cytokines released by metabolically active visceral fat, which result in chronic hyperinsulinemia and increase risk of insulin-like growth factormediated carcinonogenesis (44). Exercise decreases visceral fat, lowering the level of carcinogenic adipocytokines, improves insulin sensitivity and reduces fasting insulin and C-peptide levels, and may decrease insulin-like growth factor-I (12).…”
Section: Mechanism Of Actionmentioning
confidence: 99%